2013
DOI: 10.1039/c3dt51887f
|View full text |Cite
|
Sign up to set email alerts
|

Shape-controlled solvothermal synthesis of Bi2S3 for photocatalytic reduction of CO2 to methyl formate in methanol

Abstract: Different shape of bismuth sulfide (Bi2S3), including nanoparticles, and urchin-like, microspheres hierarchical nanostructures, have been successfully fabricated using a facile and template-free solvothermal method. Their crystal and porous structures, morphologies, as well as the optical absorption were characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-vis diffuse reflection spectroscopy (DRS) and nitrogen sorption. The electron microscopy observations showed that both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…The same research group also showed that when coupled with the oxidation of acetylacetone by photogenerated holes from its valence band, photocatalytic CO 2 reduction on ZnS would lead to the formation of carboxylic acids 138. In addition to above compounds, other sulfides and solid solutions were also investigated 139, 140, 141, 142…”
Section: Photocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…The same research group also showed that when coupled with the oxidation of acetylacetone by photogenerated holes from its valence band, photocatalytic CO 2 reduction on ZnS would lead to the formation of carboxylic acids 138. In addition to above compounds, other sulfides and solid solutions were also investigated 139, 140, 141, 142…”
Section: Photocatalytic Materials For Co2 Reductionmentioning
confidence: 99%
“…The significantly enhanced activity can be attributed to the improved surface area and high CO 2 adsorption capacity. Bi 2 S 3 microspheres also showed the higher activity for photocatalytic reduction of CO 2 to methyl formate in methanol due to their special hierarchical structure, good permeability and high light-harvesting capacity, as compared with Bi 2 S 3 NPs [94].…”
Section: Nanostructured Photocatalystsmentioning
confidence: 99%
“…Meanwhile, Frei and coworkers [92,93] demonstrated that formic acid is the primary 2-electron reduction product of CO 2 at the excited Ti centers of Ti silicalite molecular sieve using methanol as electron donor, while CO is the single-photon, 2-electron-transfer reduction product of CO 2 at framework Ti centers with H 2 O acting as an electron donor. Moreover, methyl formate was also mainly produced for photocatalytic reduction of CO 2 over some other photocatalysts (such as Bi 2 S 3 [94], CuO-TiO 2 [95], Ni-doped ZnS [96] and Ag Loaded SrTiO 3 [49]) in methanol solution. Therefore, the two-electron, two-proton reaction steps from methanol or formic acid to hydrocarbons on most semiconductors seem to be impossible in many systems.…”
Section: Mechanism and Kinetics Of Photocatalytic Co 2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, alternative anode materials with higher capacity have been developed, such as Si, 4 Sn, 5 metal oxides, 6 and metal sulfides. 7 As a typical metal sulfide, Bi 2 S 3 has been widely used in many fields, such as optics, 8,9 photoelectricity, 10,11 photocatalysis, 12,13 and biology. 14,15 Due to its lamellar structure, Bi 2 S 3 is also investigated as an ideal host for hydrogen 16,17 and lithium storage.…”
mentioning
confidence: 99%